Plaque REgression with Cholesterol absorption Inhibitor or Synthesis inhibitor Evaluated by IntraVascular UltraSound (PRECISE-IVUS Trial): Study protocol for a randomized controlled trial. Issue 4 (October 2015) - Tsujita, Kenichi; Sugiyama, Seigo; Sumida, Hitoshi; Shimomura, Hideki; Yamashita, Takuro; Yamanaga, Kenshi; Komura, Naohiro; Sakamoto, Kenji; Ono, Takamichi; Oka, Hideki; Nakao, Koichi; Nakamura, Sunao; et al.
Abstract Background Although the positive association between achieved low-density lipoprotein cholesterol (LDL-C) level and the risk of coronary artery disease (CAD) has been confirmed by randomized studies with statins, many patients remain at high residual risk of events suggesting the necessity of novel pharmacologic strategies. The combination of ezetimibe/statin produces greater reductions in LDL-C compared to statin monotherapy. Purpose The Plaque REgression with Cholesterol absorption Inhibitor or Synthesis inhibitor Evaluated by IntraVascular UltraSound (PRECISE-IVUS) trial was aimed at evaluating the effects of ezetimibe addition to atorvastatin, compared with atorvastatin monotherapy, on coronary plaque regression and change in lipid profile in patients with CAD. Methods The study is a prospective, randomized, controlled, multicenter study. The eligible patients undergoing IVUS-guided percutaneous coronary intervention will be randomly assigned to receive either atorvastatin alone or atorvastatin plus ezetimibe (10 mg) daily using a web-based randomization software. The dosage of atorvastatin will be increased by titration within the usual dose range with a treatment goal of lowering LDL-C below 70 mg/dL based on consecutive measures of LDL-C at follow-up visits. IVUS will be performed at baseline and 9–12 months follow-up time point at participating cardiovascular centers. The primary endpoint will be the nominal change in percent coronary atheroma volume measured by volumetric IVUS analysis. Conclusion PRECISE-IVUS will assess whether the efficacy of combination of ezetimibe/atorvastatin is noninferior to atorvastatin monotherapy for coronary plaque reduction, and will translate into increased clinical benefit of dual lipid-lowering strategy in a Japanese population.